MODEL MANAJEMEN PARTISIPATIF UNTUK PENGEMBANGAN EKONOMI LOKAL BERBASIS KOMUNITAS - Ahmad Jet Alamin A; Margono Margono; Juanda Bancin (Yayasan Nusantara Hasana Berdikari, 2025)
This Community Service (PkM) project designed and tested a participatory management model for community-based local economic development. Common challenges include program planning that is not data-driven, uneven community participation, poorly managed local commodity value chains, weak economic institutions (business groups/village-owned enterprises/cooperatives), and limited access to markets and financing. Interventions were carried out through asset and needs mapping (participatory rural appraisal/PRA), the formation of a joint decision-making forum, the drafting of a local economic action plan, the strengthening of governance (SOPs, roles, transparency), assistance with the implementation of priority programs (pilot), and indicator-based monitoring and evaluation. Outputs include model documents and SOPs, a map of local economic potential, a one-year action plan, community accountability mechanisms, and replicable pilot results.